Replacing Styrene with Bio-derived Alternatives in Polyesters. Issue 1 (26th February 2015) - Sellars, Andrew; Clark, Andrew; Youngblood, Jeffrey P.; Coles, Stuart
Abstract : Composites offer high strength and stiffness at a lower density compared to other structural materials, therefore are of growing use to light-weight a variety of structures in order to reduce emissions and improve performance. However, traditional composites have the highest embodied carbon content of all engineering materials with limited methods of recycling. Therefore moving composites to a bio-based sourcing can have a large impact in the eco-footprint of these materials. 2-methoxy-4-vinylphenol has previously been shown to be sustainably biosourced from microbial degradation of lignin and has been termed "biostyrene". In this work, we investigate the use of 2-methoxy-4-vinylphenol analogues as a replacement for styrene as a reactive thinner for thermoset polyester that is commonly used in fibreglass composite. 2-methoxy-4-vinylphenyl acetate and 2-methoxy-4-vinylphenyl oleate were synthesized and along with unmodified 2-methoxy-4-vinylphenol and 1, 2-dimethoxy-4-vinylbenzene (3, 4-dimethoxystyrene) were compared to styrene in typical polyester formulations. Mechanical properties via tensile tests, water uptake tests, and thermal properties via dynamic scanning calorimetry were used for comparison. Overall, solubility issues were apparent using the biostyrenes, however, blends of biostyrenes with styrene of up to 50% showed no statistical difference with pure styrene in properties and so may be a viable styrene replacement in polyester used for fibreglass.